The Application of the Ultimum Remedium Principle in the Handling of Minor Crimes in Indonesia - Mery Rohana Lisbeth Sibarani; Aribandi; Aliman; Ade Ari Gumilar; Liza Utama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The principle of ultimum remedium serves as a fundamental concept in criminal law, emphasizing that criminal sanctions should be the final recourse after other legal remedies are deemed insufficient. This doctrine arises from the understanding that criminal law is inherently repressive and should only be employed when non-penal approaches fail to resolve legal issues. In Indonesia, the application of this principle in handling minor criminal offenses remains problematic. Although recent legal reforms have begun to incorporate restorative justice mechanisms, punitive approaches still dominate in practice. Many individuals committing petty crimes continue to be prosecuted through formal judicial proceedings and subjected to imprisonment, despite the relatively minor harm caused. This study explores the extent to which the ultimum remedium principle has been implemented in the enforcement of minor criminal offenses in Indonesia. It also examines the challenges hindering its effective application and offers potential policy recommendations. Using a normative juridical approach, this research analyzes statutory provisions and relevant case studies. The findings indicate that the principle has not been fully realized, primarily due to inconsistent enforcement practices among law enforcement officials and the underdevelopment of alternative dispute resolution frameworks outside the court system.